2012
DOI: 10.1371/journal.pone.0042959
|View full text |Cite
|
Sign up to set email alerts
|

Different Subtypes of GABA-A Receptors Are Expressed in Human, Mouse and Rat T Lymphocytes

Abstract: γ-aminobutyric acid (GABA) is the most prominent neuroinhibitory transmitter in the brain, where it activates neuronal GABA-A receptors (GABA-A channels) located at synapses and outside of synapses. The GABA-A receptors are primary targets of many clinically useful drugs. In recent years, GABA has been shown to act as an immunomodulatory molecule. We have examined in human, mouse and rat CD4+ and CD8+ T cells which subunit isoforms of the GABA-A channels are expressed. The channel physiology and drug specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 40 publications
3
86
1
Order By: Relevance
“…This is consistent with the in vitro studies of Han et al (2007) that found that pro-inflammatory effects of ENDO -mediated through NF-jB -increased host levels of TNFa, IL-6, IL-1b and iNOS, and another study that found that activation of the GABA receptor (a major target of OC pesticides; Rand et al 2010) enhanced synthesis of IL-6 and TNFa (Reyes-Garc ıa et al 2007). Mendu et al (2012) confirmed the presence of the GABAergic system in mammalian immune cells. It is known that patients with CRC have elevated levels of IL-6 in the serum and that these concentrations correlate with an increase of this cytokine in tumor tissues.…”
Section: Discussionsupporting
confidence: 58%
“…This is consistent with the in vitro studies of Han et al (2007) that found that pro-inflammatory effects of ENDO -mediated through NF-jB -increased host levels of TNFa, IL-6, IL-1b and iNOS, and another study that found that activation of the GABA receptor (a major target of OC pesticides; Rand et al 2010) enhanced synthesis of IL-6 and TNFa (Reyes-Garc ıa et al 2007). Mendu et al (2012) confirmed the presence of the GABAergic system in mammalian immune cells. It is known that patients with CRC have elevated levels of IL-6 in the serum and that these concentrations correlate with an increase of this cytokine in tumor tissues.…”
Section: Discussionsupporting
confidence: 58%
“…Although GABA has been described as neuroprotective by acting directly on GABA B Rs expressed on neurons (Fern et al 1995), it has recently been suggested that, by acting on cells different of neurons, this neurotransmitter may have beneficial effects by reducing neuroinflammation. In support of this notion, it has been reported the expression of GABA A Rs on CD4+ T-cells from mouse, rat and human origin (Mendu et al 2012). Interestingly, CD4+ T-cells not only sense GABA on the environment but they can also produce it and release it (Bhat et al 2010).…”
Section: Neurotransmitters As Modulators Of Encephalitogenic T-cellsmentioning
confidence: 82%
“…, and CD8 ? T cells [23]. Up to now, if there is any correlation between the expressions of GABA-A receptors on human T cells and seizure development remains totally unknown.…”
Section: Changes Of Pbcs After Epileptic Seizurementioning
confidence: 99%